URGENSI KLAUSUL NON-PRECLUDED MEASURES DALAM BILATERAL INVESTMENT TREATY INDONESIA - Sefriani Sefriani (Faculty of Law, Universitas Padjadjaran, 2019)
AbstractThe legitimacy crisis of the Bilateral Investment Treaty (BIT) within the international community was caused by the increasing regulatory disputes before the Investor-State Dispute Settlement (ISDS) forum. It encourages Indonesia to discontinue several BITs, to review and to make new BIT models for Indonesia. This article aims to analyze the urgency of the non-precluding measures (NPM) clause in the new BIT Model of Indonesia to balance the interests of investors and the interests of Indonesia as the host state, considering that to date the existing BIT content is not balanced. The BIT provides so much protection to investors and, vice versa, weighty obligations to the host country. This study employed descriptive analytical method. The study concludes that the NPM Clause is very important in the new Indonesian BIT Model. At least, can be based on five arguments. First, the NPM clause will transfer risk from the country to foreign investors in situations of extraordinary threats. Second, the NPM clause will limit investor protection in certain situations. Third, the NPM clause will provide greater flexibility to Indonesia as the host to regulate its investment policy to achieve sustainable development to realize the people’s welfare, labor rights, public health, safety environment, public morals, and order. Fourth, the NPM clause is important for self-recovery during international financial crisis. Fifth, lastly, the NPM clause will balance the protection of both investors and Indonesia as the host state.Urgensi Klausul Non-Precluded Measures dalam Bilateral Investment Treaty IndonesiaAbstrakKrisis legitimasi terhadap Bilateral Investment Treaty ( BIT) di masyarakat internasional yang disebabkan antara lain oleh semakin meningkatnya regulatory disputes, di forum Investor- State Dispute Settlement (ISDS), mendorong Indonesia memberhentikan berlakunya beberapa BIT, meninjau ulan dan membuat model BIT yang baru untuk Indonesia. Artikel ini bertujuan untuk menganalisis urgensi klausul non precluding measures (NPM) dalam BIT Indonesia yang baru untuk menyeimbangkan kepentingan investor dengan kepentingan Indonesia selaku tuan rumah (host state) mengingat selama ini kandungan BIT tidaklah imbang. BIT memberikan perlindungan yang begitu besar pada investor dan sebaliknya kewajiban yang begitu berat kepada negara tuan rumah. Metode analisis yang digunakan adalah deskriptif analitis. Hasil kajian yang dilakukan penulis menyimpulkan bahwa Klausula NPM sangat penting untuk dimasukkan dalam Model BIT Indonesia yang baru, berdasarkan 5 argumen yaitu bahwa: klausula NPM akan mengalihkan resiko dari negara ke investor asing Dalam situasi adanya ancaman yang luar biasa,; klausul NPM akan membatasi perlindungan investor dalam situasi-situasi tertentu; Klausul NPM akan memberikan fleksibilitas yang lebih besar kepada Indonesia selaku tuan rumah untuk mengatur kebijakan investasinya dalam rangka mencapai pembangunan yang berkelanjutan (sustainable development) untuk mewujudkan kesejahteraan masyarakatnya, melindungi hak-hak buruh, kesehatan masyarakat, keselamatan, lingkungan, moral publik atau ketertiban umum; Klausul NPM penting untuk pemulihan diri manakala mengalami krisis keuangan internasional; dan bahwa Klausul NPM akan menyeimbangkan antara perlindungan terhadap investor dengan perlindungan terhadap Indonesia sebagai host state.DOI: https://doi.org/10.22304/pjih.v6n2.a2